Digital Financial Inclusion and the Sales Performance of Small and Medium Enterprises in Mukono Municipality. - Annmarie Atuhaire (Uganda Christian University, 2023)
The study sought to examine the effect of digital financial inclusion on the sales performance of small and medium enterprises in Mukono Municipality. The study was guided by three objectives: examining the contribution of mobile phone banking on the performance of SMEs, establishing the contribution of internet banking on the sales performance of SMEs and finding out the contribution of agency banking on the performance of SMEs in Mukono Municipality. The study was carried out using cross-sectional survey research design where quantitative research approach was utilized. Stratified sampling method was used to get a sample of 44 respondents who were SME owners of the selected businesses dealing in boutiques, saloons, stationary bureaus, garages, restaurants, bars groceries and agricultural products in Kauga, Mukono Municipality and these responded to the questionnaires that were used to collect data. The findings of this study collectively emphasize the significant and positive impact of digital financial inclusion, including mobile phone banking, internet banking, and agency banking, on the sales performance of SMEs in Mukono Municipality. Business owners in the region recognize the convenience, efficiency, and security offered by these banking channels, which not only streamline financial operations but also reduce costs. The strong and positive correlations between each form of digital banking and SMEs’ sales performance, as evidenced by Pearson's correlation analysis, underscore the vital role these services play in enhancing business performance. These findings emphasize the growing importance of enhancing digital financial inclusion in supporting the growth and sustainability of small and medium-sized enterprises in the Mukono Municipality and potentially in similar contexts elsewhere. Finally, the study recommended that policymakers and financial institutions should actively promote digital financial services through awareness campaigns and incentives. Investing in financial literacy programs is crucial to empower SMEs in effectively using these services. Collaboration between stakeholders, including government and telecom providers, should focus on improving network infrastructure.
This is a dissertation.